2010
DOI: 10.1242/dev.042226
|View full text |Cite
|
Sign up to set email alerts
|

vHNF1 functions in distinct regulatory circuits to control ureteric bud branching and early nephrogenesis

Abstract: Mouse metanephric kidney development begins with the induction of the ureteric bud (UB) from the caudal portion of the Wolffian duct by metanephric mesenchymal signals. While the UB undergoes branching morphogenesis to generate the entire urinary collecting system and the ureter, factors secreted by the UB tips induce surrounding mesenchymal cells to convert into epithelia and form the nephrons, the functional units of the kidney. Epithelial branching morphogenesis and nephrogenesis are therefore tightly orche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
99
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(111 citation statements)
references
References 51 publications
12
99
0
Order By: Relevance
“…In agreement with previous studies (Harding et al, 2011;Lokmane et al, 2010;McMahon et al, 2008), immunofluorescence experiments showed that HNF1β was not expressed in cap mesenchyme ( Fig. 2A, arrow).…”
Section: Research Articlesupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous studies (Harding et al, 2011;Lokmane et al, 2010;McMahon et al, 2008), immunofluorescence experiments showed that HNF1β was not expressed in cap mesenchyme ( Fig. 2A, arrow).…”
Section: Research Articlesupporting
confidence: 93%
“…For instance, it has been shown that germline inactivation of Hnf1b is embryonic lethal (E7.5) (Barbacci et al, 1999;Coffinier et al, 1999a). During kidney development, the lack of this gene in the UB leads to defective UB branching and to the absence of mesenchymal to epithelial transition due to defective expression of key genes including Wnt9b (Lokmane et al, 2010) (our unpublished observations). In parallel, it has been shown that deletion of Hnf1b in already formed, still elongating, tubular segments leads to a severe polycystic kidney phenotype (Gresh et al, 2004;Verdeguer et al, 2010).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…30,31 Prominent ND/UB apoptosis and impaired UB formation occurs in embryos lacking HNF1B (also known as vHNF). 32 This transcription factor is normally expressed in the ND/UB, where it may directly upregulate PAX2. 32 …”
Section: Molecule Abbreviation Boxmentioning
confidence: 99%
“…32 This transcription factor is normally expressed in the ND/UB, where it may directly upregulate PAX2. 32 …”
Section: Molecule Abbreviation Boxmentioning
confidence: 99%